ANALYSIS OF FOREIGNER REPORTING APPLICATIONS WITH DELONE AND MCLEAN MODELS (CASE STUDY OF CLASS I IMMIGRATION OFFICE NON TPI PEMALANG) - Catur Susaningsih; Gunawan Ari Nursanto; Subkhi Mubarok (Polteknik Imigrasi, 2021)
The development of information and communication technology is happening so very fast and is driven by the human need to help get the job done.Directorate General of Immigration is one of the government agencies that implement the use of information and communication technology, the use of such technology is expected to be able to help the duties and functions of Immigration. One of the functions of Immigration is as a state security, in that it is realized by supervision.In this case, the supervision in question is for foreign nationals not only the process of entry and exit, but concerns the existence and activity while in the territory of Indonesia.In 2015 the Directorate General of Immigration released a Foreign Reporting Application (APOA) with the aim of facilitating the reporting of foreigners to the Immigration office. The use of the application has been running in all Immigration offices, but at the Imigrasi Office Class I Non TPI The use of APOA encounters obstacles in use.Therefore, the authors analyzed APOA using the DeLone and McLean models to measure the success of APOA and findout the obstacles that exist through the variables that have been determined.The results of this study concluded that the application can run well and proven to help surveillance and variables in modeling have relationships with each other.